DEVELOPMENT AND IMPLEMENTATION OF INTEGRATED LIVESTOCK AND AGRICULTURE SOLAR HOME SYSTEM FOR INDEPENDENCE OF VILLAGE ENERGY - Musyafiq, Afrizal Abdi; Zarory, Hilman; Edifikar, Wahyu (Universitas PGRI Yogyakarta, 2019)
Indonesia is one country with a large population, and most live in rural areas. The lives of people in rural areas mostly work as farmers and ranchers. The economy of rural communities still relies on agricultural crops and livestock that are sold on the market. Economic problems of rural communities arise when something interferes with crops from agriculture and livestock. The purpose of this activity is as a form of community service in the field of applying solar home system technology (SHS) to help solve the problems of the village community and create villages that are energy-based in livestock and agriculture. This community service activity was carried out at RT.05 / 12 Batangsari Hamlet, Pasarbatang Sub-District, Brebes Regency. The steps of this activity are preceded by a field assessment; focus group disscussion; and installation of SHS implementation. The result of this activity is that there are drill wells with a depth of more than 100 m and for lifting water with the help of energy-sourced water pumps from the Solar Power Plant.